Feranti Shirt Factory, Inc.: Knowing the challenges of a Philippine garments exporter - Ng, Jerry K. (Animo Repository, 1997)
With the liberalization of international trade, there are more and more global challenges confronting the worldwide garments export industry. However, challenges seem twice greater in the Philippines because of the frequent labor unrest, rising cost of raw materials importation, as well as rising labor cost relative to competing countries. Hence, garments exporters must be able to realign their strategies with the increasing demands of the foreign buyers in terms of product quality, competitive prices, and reliable turnaround time otherwise, there are big possibilities that they might lose out on the markets which theyve been assured by the quota system. Feranti Shirt Factory, Inc. has survived in the garments export industry for nearly two decades already. It was overcome the bad times during the early 90s and is gradually the early 90s and is gradually moving towards recovery. The film, however, is losing edge in the production of basic items due to cost disadvantage relative to other countries. Hence, it is currently undertaking a strategic shift towards the production of higher-end fashion items. While fashion items have higher prices, they also require more expensive costs. Therefore, Ferenti Shirt Factory, Inc. must be able to achieve overall cost leadership in order to compete in the market. It must invest heavily in productivity enhancement programs, so that manpower skills can be upgraded and machine downtime can be eliminated. These would lead to smoother production flow, lesser reworks, and higher profitability. Finally, there is also a need for the company to formalize its planning system. A multi-disciplinary planning team could allow the firm to view its environment on a wider perspective, thereby enabling it to foresee possible challenges and make contingency plan in advance. These are the basics/essential of survival in a borderless, global economy.